A High‐Performance Recycling Solution for Polystyrene Achieved by the Synthesis of Renewable Poly(thioether) Networks Derived from d‐Limonene. (19th November 2013) - Hearon, Keith; Nash, Landon D.; Rodriguez, Jennifer N.; Lonnecker, Alexander T.; Raymond, Jeffery E.; Wilson, Thomas S.; Wooley, Karen L.; Maitland, Duncan J.
Abstract : Nanocomposite polymers are prepared using a new sustainable materials synthesis process in which d ‐Limonene functions simultaneously both as a solvent for recycling polystyrene (PS) waste and as a monomer that undergoes UV‐catalyzed thiol‐ene polymerization reactions with polythiol comonomers to afford polymeric products composed of precipitated PS phases dispersed throughout elastomeric poly(thioether) networks. These blended networks exhibit mechanical properties that greatly exceed those of either polystyrene or the poly(thioether) network homopolymers alone.